Strategic Export Motives and Linking Emission Markets - Fabio Antoniou; Panos Hatzipanayotou; Nikos Tsakiris (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We explore the possibility of achieving a cooperative outcome when governments act non-cooperatively in a strategic environmental policy model where emission permit markets are linked. We introduce a specific distribution scheme of the permit revenues between the exporting countries so as to sustain the cooperative outcome as a subgame perfect Nash equilibrium. Participation in the scheme is endogenized and we show that it constitutes a subgame perfect Nash equilibrium as long as the countries are not too asymmetric. Our results are robust once we allow for multiple pollutants, different modes of competition and market power in the permits market.
Keywords: Q58; F12; F18; 330; strategic environmental policy; internationally tradable permits; cross-border pollution; imperfect competition; welfare